Interaction among the components of multiple auditory steady-state responses: enhancement in tinnitus patients, inhibition in controls - Diesch, Eugen; Andermann, Martin; Flor, Herta; Rupp, André (Neuroscience, 2010)
Amplitude and phase of steady-state signals recorded in response to amplitude-modulated (AM) sine tones vary over time, suggesting that the steady-state response (SSR) reflects not only stimulus input but also its interaction with other input streams or internally generated signals. Alterations of the interaction between simultaneous SSRs associated with tinnitus were studied by recording the magnetic field evoked by AM-tones with one of three carrier and one of three modulation frequencies. Single AM-tones were presented in single presentation mode and superpositions of three AM-tones differing in carrier and modulation frequency in multiple presentation mode. Modulation frequency-specific SSR components were recovered by bandpass filtering. Compared with single mode, in multiple mode SSR amplitude was reduced in healthy controls, but increased in tinnitus patients. Thus, while in controls multiple response components seem to reciprocally inhibit one another, in tinnitus reciprocal facilitation seems to predominate. Reciprocal inhibition was unrelated to the phase coherence among SSR components, but was correlated with the frequency of phase slips, indicating that the lateral interaction among SSR components acts in a quasi-paroxysmal manner and manifests itself in terms of a random train of phase reset events. Phase slips were more frequent in patients than controls both in single and multiple mode. Together, these findings indicate that lateral or surround inhibition of single units in auditory cortex is reduced and suggest that in-field inhibition is increased in tinnitus.
Gesehen am 02.02.2023